Patterns of Unesco's social science programme. - Hochfeld, Julian (International Social Science Journal, 1966)
The article discusses the patterns of United Nations Educational, Scientific, and Cultural Organization's (UNESCO) social science program patterns. The place of social sciences in the system of constitutional purposes and functions of UNESCO is highlighted. The activities of the social science sector of the UNESCO includes items as the encouragement of international co-operation, assistance to the appropriate organizations of scholars and researchers, promotion of teaching and training and some promotion of basic research in social sciences among others. The development of UNESCO programs was characterized both by continuities and discontinuities. The initial phase of UNESCO activities was characterized by post-war intellectual and moral preoccupations and by a relatively strong awareness of purposes and functions as formulated in the constitution. The emerging pattern of the organization, its rationale and structure is taken into consideration elaborately in the article. The organization, its field of competence and the structure of its program activities is also analyzed. The article concludes with some suggestions for improvements and modifications that can be made in the UNESCO.